Penguatan Jaringan dan Kolaborasi Antar UMKM Melalui Fasilitasi Mahasiswa PKL Diskoperindag Indramayu - Budiyanto, Tenda (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
This 30-day Community Service Program through Field Work Practice (PKL) by IAI Padhaku Indramayu students focused on strengthening networking and collaboration among Micro, Small, and Medium Enterprises (UMKM) in Indramayu Regency. Through the facilitation of PKL students placed at the Indramayu Cooperative, Small and Medium Enterprises, Trade, and Industry Office (Diskoperindag), this program aimed to identify collaboration potentials, facilitate meetings between UMKM actors, and develop networking platforms. Activities included UMKM mapping, collaboration needs analysis, organizing discussion forums, and assisting in the formation of partnerships. The results of this service indicated an increased awareness of the importance of collaboration and the formation of several collaborative initiatives among UMKM. This program also provided practical experience for students in facilitating local economic development and building networks with stakeholders.